Amyloodinum ocellatum in Dicentrarchus labrax: Study of infection in salt water and freshwater aquaponics. (October 2016) - Nozzi, Valentina; Strofaldi, Silvia; Piquer, Isabel Forner; Di Crescenzo, Davide; Olivotto, Ike; Carnevali, Oliana
Abstract: This investigation is aimed to improve the knowledge on the physiological alterations occurring at morphological and molecular level in European sea bass naturally infected by A. ocellatum and reared at different salinities. European sea bass juveniles ( Dicentrarchus labrax ) weighing 20 ± 0.5 g were divided in three aquaponics systems: CTRL, reared at 20 ppt salinity; AFI, reared in freshwater (0 ppt) and infected with the dinoflagellate Amyloodinium ocellatum ; ASI, reared at 20 ppt salinity and infected with A. ocellatum . Beta vulgaris plants were introduced in each of the aquaponic systems. Temperature was increased 1 °C every second day from 18 to 25 °C during the experiment. At the end of the trial, liver, brain, intestine and gills were sampled for molecular and histological analyses. A. ocellatum affected D. labrax growth (insulin-like growth factor I, IGF-I) and appetite (Neuropeptide Y, NPY) signals in ASI. Immune system was activated in ASI by the presence of parasites by producing higher levels of Interleukin-1 (IL-1) and Tumor Necrosis Factor α (TNFα). Peroxisome proliferator-activated receptor α (PPAR α), codifying for a protein involved in lipid metabolism, was upregulated in ASI because of the necessity to produce energy to maintain homeostasis. On the contrary, A. ocellatum did not cause signs of infection in AFI as confirmed by gene expression and histological analysis, that were similar to CTRL. However, in freshwater reared fish, a modification of lipid metabolism was observed through a reduction in PPARα gene expression and hepatic lipid content. Highlights: Amyloodinium ocellatum infection affected growth, appetite and activated the fish immune system. A. ocellatum induced morphological and molecular modification in gills and liver of fish. Freshwater modified the lipid metabolism inducing a decrease in PPARα expression. Fish infected with A. ocellatum enhanced the lipid degradation to restore the homeostasis. Properly designed aquaponics system provides a valid and rapid solution against A. ocellatum infection.